Vesicular translocation of PARP-1 to cytoplasm causes ADP-ribosylation and disassembly of vimentin filaments during microglia activation induced by LPS - Chen, Ruiqi; Xie, Lirui; Fan, Yang; Hua, Xiangmei; Chung, Chang Y. (Frontiers in Cellular Neuroscience, 2024)
ADP-ribosylation plays a significant role in various biological processes including genomic stability maintenance, transcriptional regulation, energy metabolism, and cell death. Using macrodomain pull-down assay with microglia lysates and MALDI-TOF-MS analysis, we identified vimentin as a major protein highly ADP-ribosylated by The poly(ADP-ribose) polymerases-1 (PARP-1) in response to LPS. ABT-888, a potent inhibitor of PARP-1/2 blocks the disassembly and ADP-ribosylation of vimentin.PARP-1 is a highly abundant nuclear protein. Its nuclear functions in repairing DNA damages induced by various stress signals, such as inflammatory stresses, have been well studied. In contrast, limited studies have been done on the cytoplasmic role(s) of PARP-1. Our study focuses on the cytoplasmic role of PARP-1 during microglia activation. Using immunofluorescence microscopy and western blotting, we showed that a significant amount of PARP-1 is present in the cytosol of microglia cells stimulated and activated by LPS. Live cell imaging showed the translocation of nuclear PARP-1-EGFP to the cytoplasm in vesicular structures upon LPS stimulation. ABT-888 and U0126 can block this translocation. Immunofluorescence staining with various organelle marker antibodies revealed that PARP-1 vesicles show colocalization with Lamin A/C, suggesting they might be derived from the nuclear envelope through nuclear envelope budding. In conclusion, we demonstrated that PARP-1 is translocated from the nucleus to cytoplasm via vesicles upon LPS stimulation and that cytoplasmic PARP-1 causes ADP-ribosylation and disassembly of vimentin filaments during microglia activation induced by LPS.